Labored speech: reconsidering how communication studies works. Issue 2 (3rd April 2018) - McConnell, Kathleen
ABSTRACT: This essay introduces a special issue concerned with the state of academic labor in the field of communication studies. Academics first voiced concerns about casualization and the deteriorating state of academic labor over 40 years ago. Predictions made then about the decline of tenure have become reality. A 2018 National Communication Association report found that the field of communication studies has the smallest percentage of total faculty who are either tenured or tenure-track. As academic jobs continue to casualize, the field risks its legitimacy, status, and educational and scholarly commitments by not attending to labor practices. While the problems with academic labor are well documented, alternatives remain elusive, a situation that constitutes a moment of possibility.